apoA2 correlates to gestational age with decreased apolipoproteins A2, C1, C3 and E in gestational diabetes - Stephen L Atkin; Alexandra E Butler; Abdul Badi Abou-Samra; Manjunath Ramanjaneya; Ilham Bettahi; Abu Saleh Md Moin; Lina Ahmed; Mohamed A Elrayess; Steven C Hunt (BMJ Open Diabetes Research & Care)
Introduction Pregnant women with gestational diabetes mellitus (GDM) are at risk of adverse outcomes, including gestational hypertension, pre-eclampsia, and preterm delivery. This study was undertaken to determine if apolipoprotein (apo) levels differed between pregnant women with and without GDM and if they were associated with adverse pregnancy outcome.Research design and methods Pregnant women (46 women with GDM and 26 women without diabetes (ND)) in their second trimester were enrolled in the study. Plasma apos were measured and correlated to demographic, biochemical, and pregnancy outcome data.Results apoA2, apoC1, apoC3 and apoE were lower in women with GDM compared with control women (p=0.0019, p=0.0031, p=0.0002 and p=0.015, respectively). apoA1, apoB, apoD, apoH, and apoJ levels did not differ between control women and women with GDM. Pearson bivariate analysis revealed significant correlations between gestational age at delivery and apoA2 for women with GDM and control women, and between apoA2 and apoC3 concentrations and C reactive protein (CRP) as a measure of inflammation for the whole group.Conclusions Apoproteins apoA2, apoC1, apoC3 and apoE are decreased in women with GDM and may have a role in inflammation, as apoA2 and C3 correlated with CRP. The fact that apoA2 correlated with gestational age at delivery in both control women and women with GDM raises the hypothesis that apoA2 may be used as a biomarker of premature delivery, and this warrants further investigation.